Principles to award learning achievements for lifelong learning in health using micro-credentials: an international Delphi study - Sharon Mitchell; John Hart; Muntaha Gharaibeh; Graham T. McMahon; Anthea Rhoda; Siobhan Fitzpatrick; Tana Wuliji; Janusz Janczukowicz (Human Resources for Health, 2025)
Abstract Background This research investigates micro-credentialing as an approach to recognise learning achievements in health. Establishing international standards can ensure consistency, promote equity, and enhance quality of recognition systems. Achieving stakeholder consensus on the key topic areas is an important precursor to lead to relevant topics from which to build appropriate standards. This research supports the efforts by UN agency representatives and experts in qualification systems, medical education, the health and care sector, regulation, and accreditation, to build foundations from which to launch normative work on the application of micro-credentials to award learning achievements for health and care workers. Methods A modified Delphi study following methodological steps was conducted. From April to May 2021, a literature review investigated existing standards in continuing professional development and the use of micro-credentialing in health. Results from the review informed the initial draft of statements that were then refined through three iterative Delphi rounds between May to September 2021. The process culminated in a final workshop in March 2023. Results A total of 53 participants completed the Delphi, with results analysed by researchers using qualitative analysis. Consensus was achieved on the core principles to recognise learning achievements. The expert panel agreed on the need for standards that are competency-based, and require evidence of learning indicating what a learner can do. There was also consensus that the characteristics of a valid digital award or micro-credential should be portable, standardised, secure, interoperable, stackable and verifiable. Conclusions The growing body of literature on micro-credentialing highlights its potential as a method to recognise learning achievements. The interest in alternative pathways to award health practitioners, through short competency-based micro-learning opportunities, has spurred discussions on the practical application of micro-credentials. This research outlines the categories and principles for a proposed framework to implement micro-credentialing to recognise learning achievements within the health and care sector.